If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1(2x + 4) = 15 Reorder the terms: 5 + -1(4 + 2x) = 15 5 + (4 * -1 + 2x * -1) = 15 5 + (-4 + -2x) = 15 Combine like terms: 5 + -4 = 1 1 + -2x = 15 Solving 1 + -2x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2x = 15 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 15 + -1 -2x = 15 + -1 Combine like terms: 15 + -1 = 14 -2x = 14 Divide each side by '-2'. x = -7 Simplifying x = -7
| -8(-x-7)=-x+29 | | 24y-20x=72 | | 1404=.08(x)+.04(y) | | 4(x+1)=2(x+3)-4 | | Z^2=8+6i | | 11-w=187 | | 4x+1=3(x+2)+2x | | 20.44=1.5x*x | | 2n^2+3x-9=0 | | 20x-5y=1.2 | | 0=1.5x*x | | 2/3x-5=61 | | 672=.08(x) | | 5-3(2x+2)=1-7x | | 1200-1/6 | | 5(x+3)=3x+35 | | 8r-28=6(3r+7) | | b^2=-5b | | 10g+2=2g+102 | | 6(z-4)=30 | | 3412x=18 | | 16^1/3x^3/5 | | 88=(-n+7) | | 7y=16x+30 | | (72/8)*9 | | S^2-6s-10=6 | | q=z-4n/b | | (12-8)+(9)+(25)=34 | | 3f+3w=17.70 | | 4x-4x^2=3 | | 15+p=7 | | 8x-5=9x+15 |